Pengaruh Penggunaan Media Flashcard terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam - Zaidane A, Muhammad; Alfurqan, Alfurqan (ISLAMIKA, 2024)
This exploration was roused by the absence of educator advancement in the utilization of learning media, particularly in Islamic Strict Schooling subjects. It is strongly suspected that this is a factor in students' low learning achievement. This exploration expects to look at the effect of involving cheat sheet media as an imaginative option in working on the nature of learning and at last decidedly affecting understudy scholastic accomplishment. This exploration utilizes a quantitative strategy with a semi exploratory methodology, to test variable x which includes the utilization of cheat sheet media and variable y likewise applies to understudy learning results. A purposive sampling method was used to sample the entire 54-student population. The software SPSS 26 was used to analyze the obtained data. The consequences of measurable investigation utilizing the free example t-test showed an importance worth of 0.001, which is far underneath the importance level of 0.05. This demonstrates that there is an extremely huge distinction between the normal scholastic scores of understudies in classes that utilization cheat sheet media (trial class) and classes that don't utilize cheat sheet media (control class). Based on these findings, it can be concluded that students who use flashcard materials achieve significantly higher learning outcomes.